Race and the making of American liberalism - Horton, Carol A. (OUP E-Books., 2005)
Traces the roots of the contemporary crisis of progressive liberalism into the nation's racial past. This book argues that the conservative claim that the American liberal tradition has been rooted in a conception of individual rights is inaccurate. It also shows that American liberalism has served both to support and oppose racial hierarchy.